Promoting Growth, Yield, and Phosphorus-Use Efficiency of Crops in Maize–Wheat Cropping System by Using Polymer-Coated Diammonium Phosphate. Issue 6 (26th March 2017) - Yaseen, Muhammad; Aziz, Muhammad Zahir; Manzoor, Asif; Naveed, Muhammad; Hamid, Yasir; Noor, Sobia; Khalid, Muhammad Awais
ABSTRACT: Field experiments were conducted at Institute of Soil and Environmental Sciences, University of Agriculture, Faisalabad, Pakistan, to check the effect of polymer-coated diammonium phosphate (DAP) on maize–wheat cropping system. Different rates of polymer-coated and uncoated phosphorus (P) were applied first to maize then followed by wheat after harvesting of maize on same field. Results showed that application of 100% of recommended P from polymer-coated DAP increased plant height (10%), chlorophyll content (4%), biological yield (17%), grain yield (36%), agronomic efficiency (43%), and nitrogen, phosphorus, and potassium contents of maize produces, while in case of wheat 75% recommended P from polymer-coated DAP increased plant height (6%), chlorophyll content (18%), biological yield (20%), grain yield (14%), agronomic efficiency (72%), and nitrogen, phosphorus, and potassium contents of grains and straw as compared with uncoated DAP. So, it can be summarized that polymer-coated DAP can effectively improve growth, yield, and phosphorus-use efficiency of maize and wheat crop.